Analytical tools and methods for assessing the innovative potential of construction industry enterprises in cyclic fluctuations - Halunka , Oksana; Korytko , Dmytrii; Ryzhakova, Galyna; Chupryna, Iurii; Kazmin , Oleksandr (Ways to Improve Construction Efficiency, 2025)
A set of theoretical, methodological and applied problems related to the formation and application of analytical tools and methods for assessing the innovative potential of construction industry enterprises in conditions of cyclical fluctuations of economic and industry development is considered. The relevance of the topic is due to the increasing instability of the macroeconomic environment, the strengthening of the cyclicality of investment activity in construction, the increasing role of innovations as a key factor in the economic and financial stability of enterprises, as well as the need for scientific substantiation of management decisions in the field of innovative development.The paper deepens theoretical approaches to the interpretation of the innovative potential of construction industry enterprises as a complex dynamic system, which is formed under the influence of internal resource capabilities and external cyclical factors. The feasibility of transitioning from static models of assessing innovative potential to a dynamic methodology is substantiated, which takes into account the temporal variability of potential components, the phases of the economic and industry cycle, as well as the relationship between innovative development and the economic and financial stability of enterprises.Existing analytical tools and methods for assessing innovative potential are systematized and their classification is carried out according to resource, integral, process, productive and strategically diagnostic approaches. It is proven that for construction industry enterprises, combined, adapted methods that combine quantitative and qualitative analysis tools and allow to adequately reflect the specifics of the industry and the cyclical nature of its development have the highest analytical value.A dynamic integral indicator of the innovative potential of construction industry enterprises has been developed, based on normalized indicators of resource, process and performance components and supplemented by a cyclical correction coefficient. The proposed toolkit provides the possibility of comparative and dynamic analysis of innovative potential taking into account the phases of the economic cycle and allows identifying trends in its transformation over time.Particular attention is paid to the study of the role of adaptability as a system-forming property of innovative potential. It is substantiated that it is adaptability that determines the ability of construction industry enterprises to transform innovative potential in response to external cyclical disturbances, minimize the negative consequences of economic downturns and ensure the stability of cash flows. It is proven that innovative potential with a high level of adaptability performs a stabilizing function, contributing to increasing the economic and financial stability of enterprises.The practical significance of the research results lies in the possibility of using the proposed dynamic methodology in the system of strategic and operational management of innovative development of enterprises in the construction industry, as well as in the process of substantiating investment and management decisions taking into account cyclical fluctuations in the economy. The obtained scientific results expand the theoretical and methodological principles of research on innovative potential and create a basis for further empirical and applied research in the field of innovative development of the construction industry.